Evaluación de los polifenoles extraídos a partir de residuos de Coffea Arabica, para la producción de un coagulante natural (2018)
Primary water treatment consists in 3 stages: coagulation, flocculation and sedimentation. While it is true that the three of them are important, the second and third stages depend on the first one. For coagulation process to occur, the use of a coagulant is needed and it can be chemical or natural. The research of natural compounds that supersede chemical coagulants was the investigation project main objective. Polyphenols extracted from Coffea arabica were tested on synthetic water with a turbidity of 520.90 NTU; polyphenols were extracted by ultrasound technique for 60 minutes and 40KHz; extract was quantified by Folin Ciocalteu method, throwing a concentration of 100%.